A trajetória histórico-geográfica e o contexto educacional do município de Ampére – PR - Popiolek, Camila Cristina Taschin (2022)
This research was developed in the Post-Graduation Program in Geography at the Statecolege of Western Paraná (UNIOESTE), of Francisco Beltrão, in the survey line Education and Geography Teaching, with the participation in the Research Group Representations, Spaces, Times and Languages in Educational Experiences (RETLEE). This research is the indication that emerged from the problems faced as a Geography teacher to work with the issues of place. Due to the absence of information and data about the Geography and History of the city of Ampére. It stimulated to seek historical sources and geographic data to strengthen the Geography and History teaching of Ampére. The research has the purpose of contributing to the understanding of the territory and the citizenship formation of the students, from the Initial Years of Elementary School. The research involved three stages: a) case study, carried out with 64 teachers of the Early Years of Elementary School, present in five municipality schools in the city of Ampére - PR, they are: João Bento do Couto school, Professor Leopoldo de Witt school, Dr. Caetano Munhoz da Rocha school, José Arnoldo Dresch school and Professora Nerci Fátima Delani Potrick school. The teachers participating in the research answered a questionnaire, presented and evaluated the needs and perspectives to work with Geography and History of the city of Ampére; b) analyses of bibliographic sources, mainly the minutes of the sessions of Ampére's City Council, Beltrão's Newspaper and the informative magazines of Ampére's City Hall, with the purpose of grounding and rescuing the historical-geographical context of the city; c) interview with Mr. Orlando De Toni, Ampére's first History teacher, essential to indicate and understand hidden points in the history, such as the initial organization of the town, schools, commerce and the Municipal Hydroelectric Power Plant. The research with the teachers showed the absence of pedagogical resources about the town and the difficulties to access the information. The absence of information on the period between the 1960s and the 1980s was eminent. As a result, we present a didactic material to support teachers, with the objective of fortifying the teaching and the citizenship formation of the students by means of maps, figures and graphics of the historicalgeographical context of Ampére.